Changes in sensory function and force production in adults with type II diabetes. Issue 6 (30th October 2014) - Ochoa, Nereyda; Gorniak, Stacey L.
ABSTRACT Introduction: The purpose of this study was to evaluate the relationship among sensory function, disease severity, and upper extremity force production in adults with type II diabetes (T2D) as compared with healthy age‐ and gender‐matched controls. Methods: Ten adults with T2D and 10 healthy age‐ and gender‐matched control subjects underwent a battery of sensory and motor function evaluations. Data on disease severity and duration were also collected. Results: The T2D group exhibited sensory deficits and altered force production as compared with healthy controls. Sensory function correlated with disease severity, as did signal predictability of kinetic output during submaximal force production tasks. Maximal force production tasks were associated with altered output in T2D, but these data did not correlate with disease severity or sensory dysfunction. Conclusions: Some, not all, motor performance deficits in T2D are associated with sensory dysfunction. Mechanisms responsible for these changes in adult‐onset T2D are described. Muscle Nerve 50: 984–990, 2014